Hypertension, secondary to a renal artery aneurysm, treated by ex vivo aneurysm repair and autotransplantation. (19th November 2012) - Prajapati, Hitesh; McCallum, Amy; Finlay, Eric
Abstract : Hypertension is becoming a more common problem in childhood and adolescence. About 5–10% of paediatric patients with hypertension have underlying renovascular disease. Although renal artery aneurysms (RAAs) are an uncommon cause of disease of the renal vessels, they are recognised as a cause of hypertension. We describe a 15-year-old man with symptomatic hypertension who after extensive investigation was found to have a right RAA. Our patient responded to conservative management with two antihypertensive agents, but as a young sports enthusiast, he was keen to pursue more definitive options. Complex anatomy of the aneurysm precluded the use of endovascular treatment. Surgical options were explored, and after counselling, our patient underwent a nephrectomy, ex vivo aneurysm repair and autotransplantation with which his hypertension resolved. Our case highlights the difficulty of diagnosing RAAs in hypertensive patients and that, in carefully selected patients, invasive surgical intervention of RAAs is a viable treatment option.